Apoyo en la secretaría de planeación en la alcaldía del municipio de Jericó Boyacá (2022)
The development of the internship in the secretary of planning and infrastructure of the municipal government of Jericó began, with a brief introduction about the operation of the office, citing the main functions in charge of the dependency and the work methodology adopted for the execution of the same. Boyacá, a.j. (2015). For integration into the secretariat's work team, access is granted to the organization's local area network folder, where officials and external support staff work together to create documents and disseminate information on topics agency interest. In the specific case of the internship, the shared folder will be used for the projection of the documentation requested by the secretary of planning and infrastructure according to the focus of the professional practice, such as the preparation of supervision reports during the execution stage. of the contracted projects, preparation of budgets, reports of quantities and analysis of unit prices for future contracts of the municipality, organization and cataloging of digitalized documents of the physical files of the contracts in charge of the secretary, among others.